PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN BAGIAN GUDANG PADA PT.SICEPAT EKSPRES INDONESIA CABANG PEKANBARU - Dewi, Diana Sri; Cahyono, Jeki Tri (Eko dan Bisnis: Riau Economic and Business Review, 2021)
This research was at PT.Sicepat Ekspres Indonesia - Branch Pekanbaru   in 2021. The purpose of research is know whether motivation work   significant of the performance of an employee at PT.Sicepat Ekspres Indonesia - Branch Pekanbaru.  Population in this research is population in research it is all warehouse employees of PT. Sicepat Ekspres Indonesia Pekanbaru Branch, totaling 60 people in 2021. Because population in research this is a little hence writers use of a whole population that there is to are only sampled. Based on the values t obtained t count of  5,670 while value t table was in 2,00247 which means t count = 5,670 > 2,00247 then H0 turned down and Ha received is the motivation work   of the performance of warehouse employees of at PT.Sicepat Ekspres Indonesia - Branch Pekanbaru  . The motivation work  of the performance at warehouse employees of at PT.Sicepat Ekspres Indonesia - Branch Pekanbaru of 36,1% and 63,9%  influenced by the other factors that are not pursuing in this research . The research showed that motivation work  have had a positive impact and significant of the performance at warehouse employees of at PT.Sicepat Ekspres Indonesia - Branch Pekanbaru. With the regression equation is linear simple as follows: Y = 16,138 + 0,630X.  So this research to strengthen previous studies